GASTROINTESTINAL BLEEDING AGAINST THE BACKGROUND OF NON-CIRRHOTIC PORTAL HYPERTENSION IN A PATIENT WITH MYELOFIBROSIS (CASE REPORT) - Rudyk, Diana; Tutchenko, Mykola; Besedinskyi, Mykola; Chub, Sergey; Lovin, Andrii; Ahapchenko, Ihor (Eastern Ukrainian Medical Journal, 2025)
Portal hypertension in the absence of cirrhotic transformation of the liver parenchyma is considered a rare pathology with a difficult diagnostics. Non-cirrhotic portal hypertension includes a heterogeneous group of conditions based on porto-sinusoidal vascular disease of the liver and chronic portal vein thrombosis. For a long time, the course of the disease can remain asymptomatic and is usually manifested by the development of one of the complications of portal hypertension. One of the most dangerous and often fatal complications is bleeding from varicose veins of the esophagus and stomach. The purpose of this article is to demonstrate, using the example of a clinical case, the peculiarities of diagnosis and methods of successful treatment of bleeding from esophageal phlebectasia in case of non-cirrhotic portal hypertension caused by splenic vein thrombosis. The article describes the clinical case of a 57-year-old patient with a bleeding from esophageal varices with non-cirrhotic portal hypertension caused by splenic vein thrombosis due to myelofibrosis. The patient was urgently hospitalized with symptoms of hemorrhagic shock, which required intensive care, varix ligation and hemotransfusion therapy. After stabilization of hemodynamic parameters, the patient underwent a porto-azygos disconnection operation, which included devascularization of the distal esophagus, proximal stomach, transection of the esophagus and splenectomy. Conclusions. Myeloproliferative diseases are one of the many causes of non-cirrhotic portal hypertension, which often remain unrecognized until its decompensation. The diagnosis of non-cirrhotic portal hypertension is often difficult, which directly affects the prognosis. The authors' goal was to draw attention, raise awareness, and demonstrate the pathogenetic link between these conditions, the given clinical case of surgical treatment can be a variant of medical tactics aimed at controlling bleeding from esophageal and gastric phlebectasia. The positive feature of the performed surgical intervention is the direct impact on the source of bleeding, namely, the disconnection of the portal and caval venous systems, which ensured the cessation of blood flow through the esophageal-gastric collaterals. Taking into account the risks of anticoagulant therapy in patients with portal hypertension with Portal vein thrombosis and bleeding from varicose veins of the esophagus and stomach we recommend long-term (3–6 months) anticoagulant therapy in patients with prothrombotic conditions after porto-azygos disconnection and exclusion of “dangerous” esophageal-gastric collaterals, which makes it possible to effectively control hemorrhagic complications.